Organizational Development Implementation in the Education and Training Agency of South Sumatra Province: Challenges, Strategies, and Implications - Glisson Ihsan Gerald (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2024)
This research investigates the implementation of organizational development (OD) within the Education and Training Agency of South Sumatra Province, aiming to provide insights into strategies, successes, challenges, and opportunities for improvement within the organization. A mixed-methods approach was employed, combining qualitative data from semi-structured interviews and document analysis with quantitative data from surveys administered to agency employees. Key findings revealed the importance of leadership commitment, stakeholder engagement, capacity building, and fostering a culture of continuous improvement as core strategies in OD implementation. Successes included enhanced collaboration, improved employee morale, and enhanced service delivery, while challenges such as resistance to change, bureaucratic inertia, and resource constraints were identified as significant obstacles. These findings carry implications for both theory and practice in organizational development, suggesting the need for targeted interventions and strategic initiatives to address systemic barriers and promote organizational change and innovation. Moreover, the research highlights broader implications for the education system in South Sumatra Province, emphasizing the importance of leveraging insights to inform strategic planning, drive organizational development, and advance educational excellence and equity across the province.